The role of the sliding direction against a grooved channel texture on tool steel: An experimental study on tactile friction. (15th March 2015) - Zhang, Sheng; Rodriguez Urribarri, Adriana; Morales Hurtado, Marina; Zeng, Xiangqiong; van der Heide, Emile
Abstract: To control tactile friction, that is the friction between fingertip and counter-body, the role of surface texture is required to be unveiled and defined. In this research, an experimental approach is used based on measuring tactile friction for directional texture (grooved channel) with varying depths. For a reference surface, in this current case a polished surface from the same tool steel is compared. The experimental results are analyzed to explain the observed skin friction behavior as a function of surface texture parameters, sliding direction and applied normal load. Sliding parallel to the groove length shows greater values in COF than sliding perpendicular to the groove direction. Furthermore, parallel sliding reveals a higher dependency of COF on the depth of the grooved channel texture than perpendicular sliding. Application of the two term friction model suggests that the adhesion component of friction has greater impact on parallel than perpendicular sliding direction. According to the observations, grooved channels are well suited to control skin friction in direction dependent sliding, for moderately loaded contact situations. This experimental research contributes to the haptic perception related research, and to the development of other direction-dependent surface structures for touch.